UBVRI Photometric Analysis of the Solar-Type Eclipsing Binary TYC 3034-299-1. (11th March 2012) - Samec, Ronald G.; Jaso, Adam; White, Jesse; Faulkner, Danny R.; Blum, Nicholas; Hamme, Walter Van
Abstract : TYC 3034-0299-1 ( CVn ) is a magnetically active, contact binary, ROTSE variable. UBVR c Ic light curves are presented along with a period study and a simultaneous UBVRI light curve solution. Our light curves show eclipse amplitudes of 0.72 and 0.62 mags ( V ) in the primary and secondary eclipses. Modeled results include a dark spot region, found at longitude 51°, a 24% Roche lobe fill-out, and a mass ratio of 0.48. A total eclipse is found to occur in the secondary eclipse making TYC 3034-0299-1 a W -type (less massive star is hotter) W UMa variable.